The impact of the board of directors profile on performance and risk of listed firms - Teodósio, João Paulo Correia (2022)
This thesis investigates the impact of the Board of Directors profile on the performance and risk of listed companies. The first chapter presents a literature review on the impact of different corporate governance mechanisms on the diverse outputs of Portuguese organizations. The investigation concludes that: (1) There is a negative relationship between the size of the Boards of Directors and the performance of organizations; (2) The non-duality of the Chief Executive Officer (CEO) promotes the performance of organizations; (3) The size and independence of the Boards of Directors, as well as the non-duality of the CEO, promote an increase of information disclosure by organizations; (4) While the age of the CEO has a positive association with their compensation, the duality of the CEO has an opposite effect; (5) The independence of the Boards of Directors increases the organizations’ risk levels. The second chapter presents a literature review, at an international level, on the impact of gender diversity on the Boards of Directors and the Top Management Teams on companies’ risk exposure. The investigation allowed us to conclude that there are universal and contingency effects. Concerning the universal effects, the international literature indicates that the presence of women in these bodies and teams promotes the reduction of firms’ operational and litigation risks. The absence of directors’ gender impact on insolvency risk levels is also universal. From the perspective of the contingent effects, the correlation signs between the directors’ gender and different levels of firms’ risk (financial, manipulation, total, systematic, and idiosyncratic) vary according to the samples used. The third chapter investigates the relationship between the size and independence of the Boards of Directors and the total, systematic and idiosyncratic risk levels of non-financial firms listed on Euronext Lisbon. The results show that companies with larger and more independent Boards of Directors have higher levels of systematic risk. The fourth chapter studies the effect of independent directors' gender and nationality on the performance of non-financial firms from the Iberian stock markets. The study presents robust results that combining these two demographic characteristics in independent directors’ positions promotes the destruction of firm value.